Kajian Ilmu Pertahanan dalam Strategi Pertahanan Negara Guna Menghadapi Ancaman Teknologi Digital di Indonesia - M. H Syafi'i; A A Supriyadi; Y Prihanto; R A G Gultom (Journal on Education, 2023)
This article explains the use of people's personal data to state security data that is currently interconnected and circulating on the internet network. Regulation of the Minister of Defense No. 16 years 2010 which mandated the establishment of a digital technology defense concept in Indonesia. Data surveillance is carried out physically and logically with integrity and upholding confidentiality be able to find illegal processes. Continued with this capacity and capability improvement as a must to be able to continue to innovate and develop because over time the types of threats and challenges will change and develop. As a support, qualified digital or cyber technology system is built first. Thus, it is hoped that the cyber defense strategy in Indonesia can guarantee sovereignty and security for the nation and state. With the aim of developing human resources to meet the needs of personnel in national cybersecurity activities. The Indonesian government has realized that this development requires policy as a measurable and clear legal basis which is then followed by the establishment of a strategic cybersecurity system. Thus, it is hoped that the security of citizens in conducting activities in the digital world can be well guaranteed their rights and obligations.